Large electrocaloric effects induced by multidomain-to-monodomain transition in ferroelectrics with electrical inclusions - Huang, Cheng; Wang, Xiaojun; Zhao, Jinbo (Frontiers in Energy Research, 2023)
The electrocaloric effect (ECE) is governed by the sudden change of the polarization field in the ferroelectric phase transition near the Curie temperature. Similarly, giant ECE can be observed extensively during the domain structure transition from multidomain to single domain in Ferroelectrics. To reveal the mechanism of the effects of the electric inclusions, phase field simulation is used to investigate the electrocaloric effect (ECE) of PbTiO3 (PTO) ferroelectric solids under electric loads. The giant ECEs of ferroelectric materials containing three types of electric inclusions, namely air, silicone oil, and water, are discussed in detail under applied electric fields. The results suggest that an unusual ultrahigh negative ECE (-9.30K) and a large EC strength (∆𝑇 ∆𝐸 ⁄ = 0.237 KmMV −1 ) are achieved near room temperature (around 50°C) in ferroelectrics containing water inclusions. The results indicate that electric inclusions generate high electrostatic energy under electric loads, which breaks through the energy barrier and plays an important role in the ECE. In summary, the works may provide a better way to obtain the giant ECE and large EC strength close to room temperature by effectively regulating the dielectric constant of the electric inclusions and the increment of the applied electric field.